Astrophysics Without Black Holes, and Without Extragalactic Gamma-Ray Bursts - Wolfgang Kundt (Acta Polytechnica CTU Proceedings)
Contrary to common belief, it is argued that our Universe contains neither Black Holes, nor Extracalactic Gamma-Ray Bursts.